Desenvolvimento econômico do município de Guaporé: a agroindústria da banha e do couro (1892 1980) - Balbinot, Giovani (2014)
This research aims to analyze the economic development of the municipality of Guapore seeking outline the complex context that has involved the development of what we agree to call first cycle of agro lard and leather, outlining the various factors related to the genres of production, road structure transport, ports flow profile of the immigrant guaporense agribusiness, as well as factors related to the accumulation of capital in the commercial sphere the homes of local commerce. The geographic divisions covering the territory of the former colony and later city of Guapore. The time frame covers the years between 1892, with the founding of the colony of Guapore and 1980s, when the decay of these developments occurs refrigerators, always stressing that this temporality is often extrapolated to a better understanding of the facts. The study is organized in order to maintain a thread-based economic development, with the process of immigration and colonization run in Rio Grande do Sul, and then the second time, enter in the foundation and development of the colony, first, and the municipality of Guapore putting in relevant factors that contributed to the agro-industrial development in analysis. On the third point, the study focuses on the establishment of enterprises linked to the lard, the built and the leather tanning industry, as well as its relationship with the economic and social development of the municipality of Guapore. Finally, we seek to analyze and understand the many factors that contributed to the decay process of these developments, both in the external environment, such as difficulties in obtaining raw materials and changes in the consumer market as domestically, with difficulties in developing new genres of greater market acceptance, at which point, the historical view extrapolates temporality previously fixed, because we understand how essential to analyze all the factors that contributed to this process of economic decay